2016
DOI: 10.1515/pjvs-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the long-term application of QuikClot Combat Gauze, ChitoGauze PRO and Celox Gauze in a femoral artery injury model in swine – a preliminary study

Abstract: The purpose of this study was to examine the safety of the long-term application of QuikClot Combat Gauze, ChitoGauze PRO and Celox Gauze using a swine model. The study was conducted on nine pigs weighing approximately 30 kg, which were randomly divided into three groups. Under deep anesthesia, the pigs underwent complete transverse cutting of the femoral artery in the groin region. Hemostatic dressings were left in the wound for 24 hours. The animals were euthanized 24 hours after dressing application. In eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In hospitals, hemorrhage causes 15–25% of trauma deaths. A lot of hemostatic materials are used for hemorrhage controlling [ 3 , 4 ], which can be divided into inorganic materials [ 5 , 6 , 7 ] and organic polymer materials [ 8 ]. Inorganic materials include WoundStat, QuikClot, and Combat Gauze and polymer materials include Celox, Celox-D, HemCon, which are all commercially available products for hemostatic wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In hospitals, hemorrhage causes 15–25% of trauma deaths. A lot of hemostatic materials are used for hemorrhage controlling [ 3 , 4 ], which can be divided into inorganic materials [ 5 , 6 , 7 ] and organic polymer materials [ 8 ]. Inorganic materials include WoundStat, QuikClot, and Combat Gauze and polymer materials include Celox, Celox-D, HemCon, which are all commercially available products for hemostatic wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Safety concerns have also been raised for some local hemostatic agents [30,31]. A recent survey indicated that hemostatic agents were infrequently utilized to manage traumatic hemorrhage during the recent conflicts in Afghanistan and Iraq [137].…”
Section: Local Hemostats Under Developmentmentioning
confidence: 99%
“…Despite these great successes, there are safety concerns with the prehospital or in-combat use of local hemostatic agents [30,135,205]. Although no adverse events have been reported in human studies with the use of Combat Gauze, HemCon, Celox Gauze, Celox granules, ChitoGauze and QuikClot ACS+ [54,204], these studies are relatively short-term observational studies.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations